2011
DOI: 10.1017/s1743921311012683
|View full text |Cite
|
Sign up to set email alerts
|

Ancestors and the sun: astronomy, architecture and culture at Chaco Canyon

Abstract: Abstract. Three architectural traditions with astronomical associations have been identified among the 'Great Houses' and 'Great Kivas' of Chaco Canyon, New Mexico. Great Houses and one Great Kiva built during the height of construction activity (AD 1020-1100), the Bonito Phase, include front-facing south-southeast (SSE) orientations, and cardinal north-south and/or east-west (NS/EW) alignments. We present ethnographic material supporting our previous proposal that the SSE orientation is probably linked to mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Several previous studies have shown that the Pueblo peoples in the northern San Juan and Chaco region were engaged in detailed sky-watching [18,[48][49][50]. However, it should be pointed out that, until now, these studies have almost exclusively centered on site alignments to Sun solstices and lunar standstills, a focus that quite likely is indicative of the ethnographic preferences of our own society, and not necessarily that of the Pueblo peoples.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have shown that the Pueblo peoples in the northern San Juan and Chaco region were engaged in detailed sky-watching [18,[48][49][50]. However, it should be pointed out that, until now, these studies have almost exclusively centered on site alignments to Sun solstices and lunar standstills, a focus that quite likely is indicative of the ethnographic preferences of our own society, and not necessarily that of the Pueblo peoples.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments with flares as proxies for signaling by fire were conducted and featured in the Public Broadcasting Service (PBS) documentary Chaco Legacy (1980). Recent studies have employed GIS analyses to determine the actual visual fields associated with individual great houses or features (Dalton 2000;Doxater 2002;Dungan et al 2018;Kantner and Hobgood 2016;Munro and Malville 2011;Van Dyke et al 2016; for a trenchant review of experiential interpretations of landmarks and visibility, see Plog 2010). Collectively, these efforts reveal that outside the lower portion of Chaco Canyon, great houses often were not intervisible and, in a few cases, they do not provide extensive fields of view, whereas not surprisingly, prominent high points on mesas can provide very long lines of sight in a welter of directions.…”
Section: Intervisibility and Signalingmentioning
confidence: 99%
“…Sofaer (2007) documented alignments between great houses and solar events, in addition to the 'Sun Dagger' petroglyph on Fajada Butte that marks solstices, equinoxes and lunar standstills (Sofaer & Sinclair 1987). Pueblo Bonito itself is oriented along cardinal axes, with its exterior south/front wall extending east-west and aligned with sunset at the autumn equinox and its conspicuous interior dividing wall running north-south (Farmer 2003;Malville & Munro 2015;Munro & Malville 2011;Williamson 1987). The pueblos in the canyon also appear to be arranged in relation to each other along directional axes, reflecting a sacred geometry incorporating roads, ceremonial structures and prominent natural features (Lekson 1999;Marshall 1997;Sofaer 2007;Stein & Lekson 1992;Van Dyke 2007a;.…”
Section: Pueblo and Chacoan Directionalitymentioning
confidence: 99%
“…South-southeast-oriented kiva pilasters contain almost four times the amount of turquoise recovered from east, south, southeast and east-southeast-oriented pilasters combined, suggesting the purposeful emphasis of this specific direction during construction. This pattern could be connected to an older Ancestral Pueblo tradition in the San Juan Basin of acknowledging this direction through architecture, beginning with sixth-century CE pithouses (Hayes 1981;Munro & Malville 2011). Five of the seven great houses founded in the late ninth and tenth centuries CE in the canyon have south-southeast orientations, including Pueblo Bonito during an earlier stage of construction (with a front-facing orientation of 161°).…”
Section: Colour and Landscapementioning
confidence: 99%